(3QhM GdHjGf aj JaSjQ GdbQBfs - (3GdESdGeHhdj GdMfaj GdNdhJj, CHh GdaOGA, ESeGYjd Mbj Hf eUWai, J (B1127 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj GXgQ ef fSNI MbGFbg GdPGJjI GdceGdjI fbhT GdYhGde hGdGYdGe hbO cGf efi Mjf GfJhGA GdGbGeI HHYV OjGQ GdQhe HYV UMGFa edJbWI ef UaMGJ GdJaGSjQ (B[(3hbO LGA aj b (B374 (3H(B] (3eG fUg (B: (3hgh gPG GdLeY GdeSei HQhM GdHjGf aj JaSjQ GdbQBfs
(3BNQgG (B:s
(3hgh Gf HYV GdeJbOejf LYd GdbQBf CKdGKG aGdKdK GdGhd jfJgi YfO bhdg ai ShQI GdJhHI nhnbnYnO GnqdpPjnf ncnPoHhG Gdnqdng nhnQoShndog hGdKdK GdKGfj YfO bhdg ai ShQI GdYfcHhJ pEnqdG pHGnqdpJj pgnj nCrMnSof hYfO GdYGeI GdKdK GdChd jfJgi YfO bhdg JYGdi nhnWnHnY Gdnqdog nYdi obodhpHpgres
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 313s
(3eYLe GdeDdajf (B1 / 362s
(3EjVGM Gdecfhf (B1 / 74 - 409s
(3gOjI GdYGQajf (B1 / 219s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs